2011
DOI: 10.1111/j.1875-595x.2011.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Self medication for oral health problems in Cameroon

Abstract: The majority of the respondents self-medicated for oral health problems. Unmarried, urban residents, aged 21-30 years reported significantly increased self-medication for oral health problems. Evidently dangerous substances were utilised for self-medication in this study, necessitating awareness and other forms of intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
62
3
19

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(104 citation statements)
references
References 27 publications
20
62
3
19
Order By: Relevance
“…In developing countries common sources of antimalarials used for self treatment were street and village shops and this could account for up to half of antimalarial drug distribution 119. Recent studies in Nigeria and Cameroun 24,29 agrees with the above showing that the hospital/pharmacy, patent /road side medicine dealers, and local hawkers/mobile drug vendors and native healers were the commonest sources.…”
Section: Self Medication -Places Where Drugs Are Obtained and Sourcessupporting
confidence: 60%
See 4 more Smart Citations
“…In developing countries common sources of antimalarials used for self treatment were street and village shops and this could account for up to half of antimalarial drug distribution 119. Recent studies in Nigeria and Cameroun 24,29 agrees with the above showing that the hospital/pharmacy, patent /road side medicine dealers, and local hawkers/mobile drug vendors and native healers were the commonest sources.…”
Section: Self Medication -Places Where Drugs Are Obtained and Sourcessupporting
confidence: 60%
“…The younger age group engaged in self medication than the older ones 29,44,56,70,89,90 . However, some studies revealed no association between age and self medication 16,24,91,92 .…”
Section: Self Medication -Sociodemographic and Medical Factorsmentioning
confidence: 99%
See 3 more Smart Citations